Criminal Legal Protection Against Doctor Malpractice in Indonesia - Tongat (Institute of Medico-legal Publications Pvt Ltd, 2020)
One of the Human Rights elements that must be achieved in accordance with the ideals of the Indonesian people is the Health aspect, the profession as a doctor devotes his/her knowledge to the public interests, has freedom and independence which is oriented to human values in accordance with the code of ethics. In implementing the code of medical ethics, it as much as possible avoids the occurrence of medical error. The error can occur in the diagnostic stage such as error or delay in diagnosis, not implementing the appropriate examination, using an examination method that is no longer used or does not act on the examination or observation result, etc. The risk that occur if it is not carried out thoroughly and carefully, is that it will result in a fatal error. The method used in this research is the normative juridism method, namely the addition method by holding on to the applied norms or legal rules. The result in this research is the liability’s manifestation of the doctor who performs medical malpractice as a form of criminal legal protection in Indonesia, it is basically based on intentional or unintentional mistakes or negligence. If it results in the victim’s death, it is equal to murder, and if the victim does not die it is called an act of persecution with the sanction of persecution.